Validating the concept of mutational signatures with isogenic cell models - Xueqing Zou (Nature Portfolio, 2018)
As cells evolve towards malignancy, somatic mutations arise from defects in DNA damage and repair processes which are each associated with individual mutation signatures. Here the authors show it is possible to recreate cancer mutational signatures in vitro using gene editing experiments in an isogenic human-cell system.